Digital marketing strategies and SMEs performance in Tanzania: insights, impact, and implications - Hellena Mohamedy Mushi (Cogent Business & Management, 2024)
This article examines the interconnected nature of digital marketing strategies, encompassing search engine optimization, content marketing, social media marketing, email marketing, influencer marketing, paid advertising, and data analysis and the performance of small and medium enterprises (SMEs) in Tanzania which encompasses various factors, including sales growth, market share, and market development. A total of 335 small and medium-sized enterprises (SMEs) used a systematic random selection method for data collection. The necessary data was gathered by the researcher using a structured questionnaire. Partial least squares–structural equation modeling (PLS–SEM) was used in the data analysis process. The results of the study demonstrate a notable correlation between the digital marketing strategies dimension and the SMEs Performance dimensions in Mbeya City. Additionally, the article reveals that there were no observed moderation impacts of dynamic environment on digital marketing strategies and SME performance. The article emphasizes the necessity for entrepreneurs to properly utilize digital marketing strategies. This article provides significant insights for scholars and practitioners interested in utilizing digital marketing methods to enhance the performance of SMEs in Tanzania. These insights are derived from a comprehensive synthesis of the most recent research in the field. Research for future studies was recommended.
Keywords: 650; Digital marketing strategies; SMEs performance; Tanzania; Dynamic environment; PLS-SEM